Trust, Commitment and Competitive Advantage in SMEs Export Performance - Md Daud Ismail; Syed Shah Alam; Roshayati bt Abdul Hamid (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
The entry of small businesses into international markets has intensified. However, despite the growing presence of small businesses in international markets, studies into their international behavior, particularly regarding the effect of international relationships on international outcomes, remain limited. This study investigates the cross-border relationships of Small and Medium Enterprises (SMEs) by examining the effects of the dimensions of the key relationship on the competitive advantage and performance of SMEs in export markets. These dimensions include trust and commitment. Results indicate that trust is significantly related to commitment and export performance. Commitment is positively related to competitive advantage but not to export performance. Trust affects competitive advantage through commitment. The effect of commitment on export performance is mediated by competitive advantage. The methodology and results are presented. The conclusion, implications, and limitations of this study are also discussed.